The SWOT Matrix and its Subdimensions: A Conceptual Innovation Proposal (Research, Society and Development, 2021)
The present work endeavours to propose a reinterpretation of the SWOT Matrix, through a new model adapted to modern organizations’ demands and renovations, focusing on a more robust and specific definition of its categories – strengths, weaknesses, opportunities and threats. The research was divided into two stages: i) bibliographic and documentary research; and ii) action research with participant observation. It took place in a British company specialised in business intelligence between the years of 2014 to 2016, wherein the progress of the utilization and adaptation of the SWOT analysis to the competitive demands of the organization was evaluated. Based on documentary and empirical evidence, the authors proposed a re-reading of the SWOT Matrix in which each category is divided into five subcategories, offering guidance to support a more robust analysis. The strengths and weaknesses are divided into the following categories: i) symptomatic; ii) asleep; iii) constant; iv) circumstantial; and iv) tangible. Opportunities are divided into the following categories: i) explored; ii) temporary; iii) wasted; iv) inaccessible; and v) disguised. Finally, threats were classified as i) constant; ii) temporary; iii) asleep; iv) provoked; and v) disguised.The article contributes to the literature and practice of strategic management by offering an alternative to address the difficulties in defining the categories within the SWOT Matrix, creating subcategories not previously raised in the literature so that it can embrace with more precision strengths and weaknesses and better evaluate opportunities and threats, thus validating the continued use of this tool.